2022
DOI: 10.1186/s12893-022-01590-3
|View full text |Cite
|
Sign up to set email alerts
|

Pedicled frontal periosteal rescue flap via eyebrow incision for skull base reconstruction (SevEN-002)

Abstract: Purpose Cerebrospinal fluid (CSF) leakage is one of the major complications after endoscopic endonasal surgery. The reconstructive nasoseptal flap is widely used to repair CSF leakage. However, it could not be utilized in all cases; thus, there was a need for an alternative. We developed a pericranial rescue flap that could cover both sellar and anterior skull base defects via the endonasal approach. A modified surgical technique that did not violate the frontal sinus and cause cosmetic problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It was observed that the average dimensions of this flap were 11.5 cm to 3.2 cm, which was large enough to reconstruct and repair the defects of the anterior skull base. These minimally invasive pericranial flaps also resolved the issue of CSF leakage [21]. Table 1 depicts the outcome of various surgeries performed using the rescue flap techniques.…”
Section: Surgical Techniquementioning
confidence: 99%
“…It was observed that the average dimensions of this flap were 11.5 cm to 3.2 cm, which was large enough to reconstruct and repair the defects of the anterior skull base. These minimally invasive pericranial flaps also resolved the issue of CSF leakage [21]. Table 1 depicts the outcome of various surgeries performed using the rescue flap techniques.…”
Section: Surgical Techniquementioning
confidence: 99%